DETERMINATION OF THE FASTEST ROUTE FOR FIRE TRUCKS IN CIREBON CITY BASED ON DISTANCE, TIME, CONGESTION AND LAND USE - Mira Lestira Hariani; Yackob Astor (FAKULTAS TEKNNIK UNIVERSITAS SWADAYA GUNUNG JATI, 2021)
Fire fighter performance can be represented by the speed of handling the fire case, where greatly influenced by the travel speed of the fire trucks to the fire location. This study aims to determine the fastest route for fire trucks in Cirebon City based on the travel distance, time, congestion and land use. The method used in this study is by applying the Geographic Information System (GIS) model in identifying several variables that affect the travel speed of fire trucks. In this study, several alternative routes were determined from the fire station (Harjamukti fire station and Bima fire station) to the location of fire (Harjamukti Market) and then calculated the travel time on each alternative route by considering travel distance, time, congestion and land use. The results showed that the fastest travel time for fire trucks in Cirebon City was largely influenced by the travel distance. However, in conditions of high traffic flow, a route with a longer distance but does not cross a congested road segment can produce a faster travel time when compared to a shorter route but crosses congested roads. The fastest route from the Bima fire station to Harjamukti market is route 1 (2,854 m) in the morning, route 3 (3,019 m) in the afternoon and evening. Meanwhile, the fastest route from the Harjamukti fire station to Harjamukti Market is Route 1 (2,069 m) in the morning, afternoon and evening because it has the shortest distance.